2018
DOI: 10.1111/1471-0528.15503
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Nifedipine alone or combined with sildenafil citrate for management of threatened preterm labour: a randomised trial

Abstract: Objective To study the tocolytic action of nifedipine combined with sildenafil citrate (SC) and if the combination is superior to nifedipine alone in inhibiting threatened preterm labour (PTL). Design Prospective randomised study. Setting An Egyptian university hospital. Population Women with threatened PTL who received either nifedipine with SC or nifedipine alone. Methods Patients were randomly allocated to receive either (1) nifedipine 20 mg orally (stat dose), followed by 10 mg orally every 6–8 hours at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Maher et al in their trial had shown superior tocolytic effect of nifedipine and sildenafil citrate combination to that of nifedipine alone. 2 In current study we have also observed superior efficacy of nifedipine and sildenafil citrate combination as compared to nifedipine alone in terms of inhibiting preterm labour and improving perinatal outcomes.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Maher et al in their trial had shown superior tocolytic effect of nifedipine and sildenafil citrate combination to that of nifedipine alone. 2 In current study we have also observed superior efficacy of nifedipine and sildenafil citrate combination as compared to nifedipine alone in terms of inhibiting preterm labour and improving perinatal outcomes.…”
Section: Discussionsupporting
confidence: 66%
“…12 Maher et al also referred higher latency in nifedipine and sildenafil citrate group. 2 In contrast, Ali et al had also documented nearly same relaxing effect of both sildenafil and nifedipine on myometrium to prevent preterm birth. 7 In recent study fewer deliveries occurred during hospitalization or within 7 days after discharge hence more women remains undelivered in combination regimen.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations